Effect of different storage conditions on grain quality of paddy - Pradip, Pradip Chandra dey; Sarmah, Angshuman; Chetia, Sanjay Kr; Medhi, Ajay Kr; Konwar, Milan Jyoti; Borah, Sanjib Ranjan; Bharali, Arunima; Baruah, Mayuri; Gummert, Martin; Khandai, Suryakanta (ORYZA-An International Journal of Rice, 2024)
The present investigation was carried out to study the physiological and biochemical changes of paddy grain (Oryza sativa L. var. Ranjit) throughout the course of a 12-month storage period, in an effort to determine the ideal storage conditions with the highest potential for storage under climacteric condition of Assam. Freshly harvested seeds of paddy grain (Ranjit) were stored under different storage conditions for a period of twelve months beginning in January. Based on the results of the study, it was found that the easily moisture permeable structures (T2, T3, T6) showed the maximum change in the physiological and biochemical parameters followed by permeable (T1 and T4) and impermeable (T5 and T7). The rate of change in the values of parameters in paddy stored in the prototype of a Grain safe™ in-store dryer (T7) was found slowest and sluggish, and maintained highest mean values amongst all the storage receptacles in respect of germination percentage, seed vigour index, head rice recovery, moisture content, total soluble protein content, starch content, total soluble sugar content, reducing sugar, non-reducing sugar and amylose content. Significant superiority of hermetic storages (T5 and T7) over traditional storage structures (T1, T2, T3, T4 and T6) in Assam irrespective of all the parameters studied was noticed. Hermetic storage was effective at blocking the effects of external humidity fluctuations as well as the spread of fungi and insects. The solar in-store drier was found to be best amongst all storage structures, in all quality aspects of the long-term storage of paddy.